FREQUENCY AND PATIENT RELATED RISKS FOR SURGICAL SITE INFECTION - Meo, Shahida , Arshad; ., Saadia Siddique; ., Qudsia Nawaz; Meo, Raabia Arshad (Pakistan Armed Forces Medical Journal, 2011)
Objective: To determine the frequency of surgical site infection (SSI) and its unknown risk factors in obstetrical and gynaecological procedures. Study Design: Descriptive study Place and Duration of Study: Obstetrics and Gynaecology department of Combined Military Hospital, Lahore from Oct 2009 to April 2010. Patients and Methods: Patients who had undergone their surgical procedures in obstetrics & Gynaecology from October 2009 to April 2010. Results: A total number of 1199 procedures were performed. Only 23 (1. 92%) got SSI. Out of these 19 (82.6%) were lower segment cesarean section and 4(17.4%) cases hysterectomies. In these infected cases, 19(82.6%) were less than 40 years of age & 4 (17.4%) cases were more than 40 years of age. Six (26.1%) patients belonged to high & 17 (73.9%) to low socioeconomic class. Nineteen (82.6%) patients weighted more than 75 kg and 4(17.4%) were less than 75 kg. Only 2(8.7%) were diabetic & 21 (91.3%) were non diabetic. Conclusion: Surgical site infection remains the commonest complication of surgery and is a burden on health care resources. It can be prevented by identifying those at higher risk and modifying skills for their care. Increasing age, obesity, Diabetes and low socioeconomic class could be the risk factors for SSI.